Targeting of dermal myofibroblasts through death receptor 5 arrests fibrosis in mouse models of scleroderma - Park, Jong-Sung; Oh, Yumin; Park, Yong Joo; Park, Ogyi; Yang, Hoseong; Slania, Stephanie; Hummers, Laura K.; Shah, Ami A.; An, Hyoung-Tae; Jang, Jiyeon; Horton, Maureen R.; Shin, Joseph; et al. (Nature Publishing Group, 2019)
Scleroderma is an autoimmune rheumatic disorder accompanied by severe fibrosis in skin and other internal organs. During scleroderma progression, resident fibroblasts undergo activation and convert to alpha-smooth muscle actin (alpha-SMA) expressing myofibroblasts (MFBs) with increased capacity to synthesize collagens and fibrogenic components. Accordingly, MFBs are a major therapeutic target for fibrosis in scleroderma and treatment with blocking MFBs could produce anti-fibrotic effects. TLY012 is an engineered human TNF-related apoptosis-inducing ligand (TRAIL) which induces selective apoptosis in transformed cells expressing its cognate death receptors (DRs). Here we report that TLY012 selectively blocks activation of dermal fibroblasts and induces DR-mediated apoptosis in alpha-SMA(+) MFBs through upregulated DR5 during its activation. In vivo, TLY012 reverses established skin fibrosis to near-normal skin architecture in mouse models of scleroderma. Thus, the TRAIL pathway plays a critical role in tissue remodeling and targeting upregulated DR5 in alpha-SMA(+) MFBs is a viable therapy for fibrosis in scleroderma.